2002
DOI: 10.4141/s02-008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of composts and liquid pig manure on CO2 and N2O emissions from a clay loam soil

Abstract: . 2002. Influence of composts and liquid pig manure on CO 2 and N 2 O emissions from a clay loam soil. Can. J. Soil. Sci. 82: 395-401. Application of raw animal manure to agricultural land has resulted in environmental and health problems. Alternatives, such as composting, are now being developed to alleviate this situation. However, very little information is available regarding the fate of composts when added to fine-textured and poorly drained soils, especially with respect to the initial decomposition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
5
14
0
3
Order By: Relevance
“…Previous studies have found that the application of liquid pig manure, liquid pig manure plus wheat straw compost and yard waste compost resulted in a decrease in the availability of inorganic N as a result of N loss through denitrification and/or N immobilization. This occurred both shortly after application (Yang et al 2002) and after an entire growing season (unpublished data). Since composts or other organic amendments usually do not supply sufficient N to meet crop needs, adding fertilizer nitrate to organic-amended soil is not uncommon.…”
Section: Mots Clésmentioning
confidence: 90%
“…Previous studies have found that the application of liquid pig manure, liquid pig manure plus wheat straw compost and yard waste compost resulted in a decrease in the availability of inorganic N as a result of N loss through denitrification and/or N immobilization. This occurred both shortly after application (Yang et al 2002) and after an entire growing season (unpublished data). Since composts or other organic amendments usually do not supply sufficient N to meet crop needs, adding fertilizer nitrate to organic-amended soil is not uncommon.…”
Section: Mots Clésmentioning
confidence: 90%
“…Since many producers in Ontario base the rate of compost addition on the ability to improve soil physical properties, we decided to compare the treatments on a dry mass basis. This also enables us to directly compare results from this study with another published studies on physical effect and greenhouse gas emissions associated with applying compost (Yang et al 2002;Reynolds et al 2003). Hence, the YWC and PMS treatments were added to the soils on a mass basis.…”
Section: Soil and Organic Amendmentsmentioning
confidence: 93%
“…in place of raw manure for soil conditioning and fertilization (Yang et al 2002). Manure treatment via composting can be active, with forced aeration, or passive, with only natural aeration and turning.…”
Section: Compostmentioning
confidence: 99%